Tophaceous Gout - Yunxin Liu; Yang Jiao (Clinical Case Reports, 2025)
ABSTRACT Chronic untreated hyperuricemia can lead to polyarticular tophaceous gout from recurrent arthritis, which could cause bone erosion and joint damage. “Overhanging edges” on X‐ray, indicative of bony erosions, are highly specific for gout. Tophaceous gout, though more common in older adults, can occur in younger individuals with prolonged hyperuricemia.